The prevention of acute recurrent otitis media - Vogazianos, Ermis (2007)
Otitis media (OM)is one of the commonest infectious diseases of childhoud, second in frequency only to the common cold. In America, acute otitis media (AOM) is the most common disease necessiating medical therapy for children younger than 5 years. There is an ongoing international debate for the importance of the factors causing OM as well as for the strategies of prevention of the disease. The pathogenesis of the disease is multi factorial making this task extremely diificult. The main aim of this study was the search of ways to prevent AOM and rAOM. This was done by examining factors that play a key role in their pathogenesis.